2018
DOI: 10.1109/tvcg.2018.2868569
|View full text |Cite
|
Sign up to set email alerts
|

Narrative and Spatial Memory for Jury Viewings in a Reconstructed Virtual Environment

Abstract: This paper showcases one way of how virtual reconstruction can be used in a courtroom. The results of a pilot study on narrative and spatial memory are presented in the context of viewing real and virtual copies of a simulated crime scene. Based on current court procedures, three different viewing options were compared: photographs, a real life visit, and a 3D virtual reconstruction of the scene viewed in a Virtual Reality headset. Participants were also given a written narrative that included the spatial loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…and virtually (i.e., VR room condition) reinstated environments, performance in the latter condition was perpetually lower than that in the former. This pattern of results is congruous with findings from studies comparing spatial memory in real and virtual environments (e.g., Lamers & Lanen, 2021;Reichherzer et al, 2018). Seeing that both real and virtual reinstatements produced significantly better spatial memory in comparison to a different or partially reinstated environment, it can be concluded that remembering locations in a virtual replica of the encoding environment may be effective, but not as efficacious as remembering in the actual encoding environment.…”
Section: Spatial Memory In Physically and Virtually Reinstated Enviro...supporting
confidence: 51%
“…and virtually (i.e., VR room condition) reinstated environments, performance in the latter condition was perpetually lower than that in the former. This pattern of results is congruous with findings from studies comparing spatial memory in real and virtual environments (e.g., Lamers & Lanen, 2021;Reichherzer et al, 2018). Seeing that both real and virtual reinstatements produced significantly better spatial memory in comparison to a different or partially reinstated environment, it can be concluded that remembering locations in a virtual replica of the encoding environment may be effective, but not as efficacious as remembering in the actual encoding environment.…”
Section: Spatial Memory In Physically and Virtually Reinstated Enviro...supporting
confidence: 51%
“…Immersion is an essential factor in the sensory fidelity of virtual environment visualisation and plays a significant role in creating a solid sense of 'presence' in the virtual space (Darken et al 2014). Such attributes have demonstrated an enhancement in environmental perception and spatial memory (Reichherzer et al 2018;Ruddle et al 2011;Reichherzer et al 2021), as well as retention of memories (Mania et al 2003). The scientific literature shows that Virtual Reality (VR) is not new to forensic science.…”
Section: Related Workmentioning
confidence: 99%
“…We found that 21% of user studies (53/248) assessed the usability of MR/AR approaches. These studies often focused on design/human factors (14/53) and involved methods such as: (a) The Slater-Usoh-Steed Questionnaire (SUS) [16,23,99] , (b) Mixed Reality Experience Questionnaire (MREQ) [97], and (c) Post Experience Questionnaire (PEQ) [97] .…”
Section: Cognitive Aspectsmentioning
confidence: 99%
“…Studies that examined memory ensured first that participants in an evaluation had a normal memory ability. To this end, they used the Automated Neuropsychological Assessment Metrics (ANAM) survey [99]. Other general methods for collecting data on the recollection of participants in evaluations of MR/AR were: (a) Free Recall, in which participants were asked to tell a narrative from their recollection; (b) Cued Recall, in which participants were asked questions to drive their recollection in order to recognize relevant points that were missing in their narrative.…”
Section: Cognitive Aspectsmentioning
confidence: 99%
See 1 more Smart Citation